Cultural Literacy Behavior Through Breakfast Together Activties to Get Healthy Living Habits in School Student - Sari, Kartika; Ardy Wiyani, Novan (International Proceedings of Nusantara Raya, 2024)
Behavioral cultural literacy is a concept that is increasingly relevant in the world of education, especially in efforts to shape students' character from an early age. One important aspect of cultural behavioral literacy is getting used to healthy living, which can start from simple activities such as having breakfast together. This study analyzes the implementation of a communal breakfast program as an effort to cultivate healthy habits among elementary school students from an axiological philosophical perspective. Through a qualitative approach, this research aims to understand the values embedded in this activity and its impact on the formation of students' character. The results show that the communal breakfast program not only meets students' nutritional needs but also instills social values such as cooperation, sharing, and mutual assistance. Additionally, this activity contributes to improving students' academic achievement. From an axiological perspective, the communal breakfast program has a high utility value in shaping healthy, intelligent, and character-driven individuals. Apart from that, the values found in breakfast together also form a spirit of responsibility and gratitude.